2007
DOI: 10.1097/mbc.0b013e3282dde994
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the tissue factor pathway inhibitor gene are not associated with ischaemic stroke

Abstract: The present study aimed to determine whether four previously described polymorphisms found within the tissue factor pathway inhibitor (TFPI) gene are associated with free plasma TFPI levels or with TFPI activity as well as the risk of ischaemic stroke in stroke patients and control individuals. We conducted a case-control study of 162 first-ever ischaemic stroke cases and 170 randomly selected community control individuals. The TFPI genotype was determined for the T-287C, C-399T, Intron 7 C-33T, and Val264Met … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Several studies have tested genetic variants in the TFPI gene and its promoter for association with TFPI plasma levels, but with conflicting results (28,(33)(34)(35). In addition, it is unclear whether genes and genetic variants outside of TFPI are associated with TFPI plasma levels in epidemiological studies.…”
Section: Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have tested genetic variants in the TFPI gene and its promoter for association with TFPI plasma levels, but with conflicting results (28,(33)(34)(35). In addition, it is unclear whether genes and genetic variants outside of TFPI are associated with TFPI plasma levels in epidemiological studies.…”
Section: Objectivesmentioning
confidence: 99%
“…Sixteen studies were of variants in the TFPI gene, with up to four variants reported in each study (Suppl. Table 3, available online at www.thrombosis-online.com) (8,9,23,24,26,28,29,31,33,34,(43)(44)(45)(46)(47)(48). One study (31), which was of rs10931292, reported insufficient data to be included in the meta-analysis.…”
Section: Included Studiesmentioning
confidence: 99%
“…96 The roles that TFPI polymorphisms may play in stroke risk are so far uncertain, and may be population dependent. 97,98 Thrombin generation accompanies the vasculopathy of atherosclerosis in the acute/subacute events in the cerebral microvasculature during ischemic stroke. This has been observed indirectly as an increase in circulating T-AT complexes.…”
Section: Systemic Coagulopathymentioning
confidence: 99%
“…Decreased TFPI concentration will increase the risk of venous thromboembolism (VTE) and myocardial infarction (MI) [ 37 , 38 ]. In this study, a total of 6 groups were included to analyze the influence of TFPI rs7586970 T/C variation on the risk of venous thrombosis caused by increased plasma TFPI concentrations [ 6 , 39 43 ]. Meta-analysis results showed that among 1829 venous thrombosis patients and normal controls, plasma TFPI concentration was significantly reduced in carriers of the rs7586970 T allele (p=0.03, OR=0.87).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that ADAMTS7 overexpression in chondrocytes upregulates TNF-α [ 28 , 29 ] and activates PDGFR-β enzyme activity. However, rs3825807 G/G genotype in vascular smooth muscle cells reduced their migratory ability, reducing their ability to recognize and phagocytize oxidized LDL (Ox-LDL) to form fatty streaks [ 39 ]. There, we postulated that vascular smooth muscle cells (VSMCs) of centenarians with the ADAMTS7 A variant may migrate into the endothelium of subcutaneous vessels, phagocytize oxidized LDL, stimulate hemichannel opening to release VLDL into the extracellular environment or adjacent cells, contributing to preventing the occurrence of atherosclerosis through the MAPK pathway.…”
Section: Discussionmentioning
confidence: 99%